2018
DOI: 10.2147/idr.s153601
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of multidrug-resistant <em>Escherichia coli</em> isolates harboring <em>bla</em><sub>CTX-M</sub> group 1 extended-spectrum &beta;-lactamases causing bacteremia and urinary tract infection in Manhi&ccedil;a, Mozambique

Abstract: BackgroundThe emergence and spread of extended-spectrum β-lactamases (ESBLs), especially CTX-M, is an important public health problem with serious implications for low-income countries where second-line treatment is often unavailable. Knowledge of the local prevalence of ESBL is critical to define appropriate empirical therapeutic strategies for multidrug-resistant (MDR) organisms. This study aimed to assess and characterize the presence of ESBL and especially CTX-M-producing Escherichia coli MDR isolates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
4
16
1
1
Order By: Relevance
“…In the study of Haba Maged (2018), TEM, SHV and CTX-M genes were found in 42.8%, 36.7% and 38.6% of cases, respectively [17]. According to the study by Elizabeth Gaviral (2018), 92% of ESBL-containing strains had the CTX-M 15 gene and the SHV gene was found in only two isolates, which indicates a high degree of consistent with this study [18]. In the Abdulaziz Qassim (2018) study, 93.94% of the strains also contained the CTX-M gene, and TEM was found in 12.12% of the strains, which is opposed with the results of this study regarding the TEM gene [7].…”
Section: Discussionsupporting
confidence: 75%
“…In the study of Haba Maged (2018), TEM, SHV and CTX-M genes were found in 42.8%, 36.7% and 38.6% of cases, respectively [17]. According to the study by Elizabeth Gaviral (2018), 92% of ESBL-containing strains had the CTX-M 15 gene and the SHV gene was found in only two isolates, which indicates a high degree of consistent with this study [18]. In the Abdulaziz Qassim (2018) study, 93.94% of the strains also contained the CTX-M gene, and TEM was found in 12.12% of the strains, which is opposed with the results of this study regarding the TEM gene [7].…”
Section: Discussionsupporting
confidence: 75%
“…The integration of mobilizable antibiotic resistance genes within the bacterial chromosome has been largely described. Thus, many transferable resistance genes, including those encoding ␤-lactamases, aminoglycoside-modifying enzymes, or trimethoprim resistance determinants, have been detected in the chromosomes of different microorganisms (141,(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196). With regard to TMQR, this finding has also been described.…”
Section: Nomenclature Of the Transferable Mechanisms Of Quinolone Resmentioning
confidence: 90%
“…The risks of the rising levels of antimicrobial resistance worldwide have been increasingly discussed and highlighted (128)(129)(130), with subsequent proposals for the implementation of different actions (128,131,132). Nevertheless, in the present century, the continuously rising global trend toward the isolation of pathogenic or nonpathogenic quinolone-resistant microorganisms has remained unaltered (55,113,(133)(134)(135)(136)(137)(138)(139)(140) and has expanded to regions with limited access to antibiotic agents (141)(142)(143). In fact, the use of quinolones has been compromised in different areas because of the high percentages of quinolone resistance among specific pathogens (134,(144)(145)(146)(147).…”
Section: Evolution Of Quinolone Resistance Over Timementioning
confidence: 99%
“…Escherichia coli displaying phenotypic ESBL activity were tested for the presence of SHV, TEM, OXA-1-like, CTX-M-2, CTX-M-3, CTX-M-8, CTX-M-9, and CTX-M-10 genes using conventional polymerase chain reaction. 22 Identified ESBL genes were not sequenced for allelic variants.…”
Section: Methodsmentioning
confidence: 99%